Complaint Service Delivery through SAPA 129 at the Regional Technical Implementation Unit for Women and Child Protection in North Sulawesi Province - Graceiella R. Tadung; Evi E. Masengi; Steven V. Tarore (JR Education, 2026)
The study focuses on the low use of the SAPA 129 digital complaint channel in comparison with direct reporting, even though violence against women and children remains a serious public issue, and digital complaint services are expected to provide safer, faster, and more accessible reporting mechanisms. Using a descriptive qualitative approach, the original research gathered data through interviews, observation, and documentation involving provincial officials, UPTD PPA personnel, SAPA 129 operators, service users, and community representatives. This research reorganizes the research result into the structure of an academic journal research and strengthens the presentation of findings through adapted tables and research result-based figures. The findings show that the service has functioned relatively well in terms of officer responsiveness and service procedure. Officers are able to receive complaints, verify identity and chronology, conduct initial assessment, and direct follow-up according to the needs of victims. Nevertheless, the use of SAPA 129 remains very low because public knowledge of the service is limited, socialization is uneven and intermittent, some users still prefer face-to-face interaction, the number of operators is insufficient, and internet connectivity sometimes disrupts the digital service process. The study argues that SAPA 129 should not be treated merely as a technological channel, but as a human-centered protection service that requires a communication strategy, adequate staffing, reliable infrastructure, inter-agency coordination, privacy assurance, and a hybrid service model. Strengthening the service, therefore, requires simultaneous improvement in outreach, staff capacity, digital infrastructure, case-management coordination, and community trust